The Impact Of Parent-Child Communication On Domestic Violence Prevention Awareness In Adolescent Mediated By Healthy Relationships - Pratiwi, Kiki; Dhamayanti, Meilani; Aras, Muhammad; Lidyana Sumolang, Mourent (CV. Inara, 2024)
Domestic violence, in general, either directly or indirectly harms the connection between a mother and her children, or between a husband and his wife. This article examines the effect of parent-child communication on domestic violence prevention awareness, the effect of healthy relationships on domestic violence prevention awareness, and the influence of parent-child communication on domestic violence prevention awareness through healthy relationships. The method used is quantitative, with survey methodology and path analysis applied in hypothesis testing. The research sample consisted of 135 adolescents aged 16-24 who were randomly selected using the Slovin formula. According to the findings, communication and a positive connection had a positive and statistically significant impact on domestic violence prevention awareness. The outcome demonstrates that communication influences domestic violence prevention awareness through healthy relationships. The findings of this study can serve as a valuable resource for parents seeking to increase their knowledge of domestic violence prevention by communicating with their children and maintaining harmonious and healthy relationships within the family.